Biliary ileus: case report - Kreve, Fernanda (2017)
Biliary ileusis a uncommon cause of mechanical bowel obstruction, affecting older adult patients who often have other significant medical conditions. It is caused by intestinal impaction of a gallstone that enters the bowel via a cholecysto-enteric fistula. The mortality rate is considerable, ranging between 12 and 27%. Treatment in most cases is surgical, aimed at the resolution of the intestinal obstruction. We report the case of a 55 year old patient diagnosed with biliary ileus, wich evolved without complications after a enterolithotomy. We have concluded, based on the literature that an early diagnosis associated with appropriate therapy can lead to a better prognosis.